Maternal mortality in the Gaza strip: a look at causes and solutions - Bӧttcher, Bettina (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Maternal mortality is an important health indicator for the overall health of a population. This study assessed the causes and contributing factors to maternal mortality that occurred in the Gaza-Strip between July 2014 and June 2015. METHODS: This is a retrospective study that used both quantitative and qualitative data. The data were collected from available medical records, investigation reports, death certificates, and field interviews with healthcare professionals as well as families. RESULTS: A total of 18 maternal mortalities occurred in Gaza between 1st July 2014 and June 30th 2015. Age at time of death ranged from 18 to 44 years, with 44.4% occurring before the age of 35 years. About 22.2% were primiparous, while 55.6% were grand multiparous women. The most common causes of death were sepsis, postpartum haemorrhage, and pulmonary embolism. The most striking deficiency was very poor medical documentation which was observed in 17 cases (94%). In addition, poor communication between doctors and women and their families or among healthcare teams was noticed in nine cases (50%). These were repeatedly described by families during interviews. Further aspects surfacing in many interviews were distrust by families towards clinicians and poor understanding of health conditions by women. Other factors included socioeconomic conditions, poor antenatal attendance and the impact of the 2014 war. Low morale among medical staff was expressed by most interviewed clinicians, as well as the fear of being blamed by families and management in case of adverse events. Substandard care and lack of appropriate supervision were also found in some cases. CONCLUSIONS: This study revealed deficiencies in maternity care, some of which were linked to the socioeconomic situation and the 2014 war. Others show poor implementation of clinical guidelines and lack of professional skills in communication and teamwork. Specialised training should be offered for clinicians in order to improve these aspects. However, the most striking deficiency was the extremely poor documentation, reflecting a lack of awareness among clinicians regarding its importance. Local policymakers should focus on systematic application of quality improvement strategies in order to achieve greater patient safety and further reductions in the maternal mortality rate.